A framework of industrial sustainability good practices - Al-Ashaab, Ahmed; Flores, Myrna; Hernando Anta, Pablo; Varro, Brigitta (Cranfield University Press, 2013)
Global environmental problems, energy and raw material prices as well as their availability, increasingly demanding legislation and environmental taxes are some of the reasons that drive the consideration of sustainability concepts and practices into company operations. This paper presents the research carried out in order to capture industrial sustainability good practices and represent them into a framework to help companies increase their awareness and adopt practices to embed them within their operational processes.
Keywords: Sustainability; Industrial Framework; Best Practices